The molecular structure, biological roles, and inhibition of plant pathogenic fungal chitin deacetylases - Mapuranga, Johannes; Chang, Jiaying; Li, Hao; Zhang, Yingdan; Li, Ruolin; Song, Lulu; Zhang, Na; Yang, Wenxiang (Frontiers in Plant Science, 2024)
Chitin/polysaccharide deacetylases belong to the carbohydrate esterases family 4 (CE4 enzymes). They play a crucial role in modifying the physiochemical characteristics of structural polysaccharides and are also involved in a wide range of biological processes such as cell fungal autolysis, spore formation, wall formation and integrity, and germling adhesion. These enzymes are mostly common in fungi, marine bacteria, and a limited number of insects. They facilitate the deacetylation of chitin which is a structural biopolymer that is abundantly found in fungal cell walls and spores and also in the cuticle and peritrophic matrices of insects. The deacetylases exhibit specificity towards a substrate containing a sequence of four GlcNAc units, with one of these units being subjected to deacetylation. Chitin deacetylation results in the formation of chitosan, which is a poor substrate for host plant chitinases, therefore it can suppress the host immune response triggered by fungal pathogens and enhance pathogen virulence and colonization. This review discusses plant pathogenic fungal chitin/polysaccharide deacetylases including their structure, substrate specificity, biological roles and some recently discovered chitin deacetylases inhibitors that can help to mitigate plant fungal diseases. This review provides fundamental knowledge that will undoubtedly lead to the rational design of novel inhibitors that target pathogenic fungal chitin deacetylases, which will also aid in the management of plant diseases, thereby safeguarding global food security.